2015
DOI: 10.1016/j.foodhyd.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of sodium alginate/d-limonene emulsions and respective calcium alginate/d-limonene beads produced by electrostatic extrusion

Abstract: Please cite this article as: Lević, S., Pajić Lijaković, I., Đorđević, V., Rac, V., Rakić, V., Šolević Knudsen, T., Pavlović, V., Bugarski, B., Nedović, V., Characterization of sodium alginate/D-limonene emulsions and respective calcium alginate/D-limonene beads produced by electrostatic extrusion, Food Hydrocolloids (2014), Abstract 17 18 In this study, calcium alginate beads immobilizing D-limonene (solid systems) have been 19 manufactured starting from emulsions of this flavor in sodium alginate (liquid sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 38 publications
6
40
0
1
Order By: Relevance
“…Extract compounds seem to fill up pores of the particles as confirmed by reduced surface area of ALG‐IN 20 ‐EXT formulation in comparison to the area of the extract‐free formulation of the same matrix composition (ALG‐IN 20 ). Recently, the similar results have been shown when the cocoa extract and D‐limonene were encapsulated in alginate beads (Lević and others ; Lupo and others ), as well as the case of T. serpyllum L. aqueous extract encapsulated in chitosan microbeads (Trifkovic and others ).…”
Section: Resultssupporting
confidence: 72%
“…Extract compounds seem to fill up pores of the particles as confirmed by reduced surface area of ALG‐IN 20 ‐EXT formulation in comparison to the area of the extract‐free formulation of the same matrix composition (ALG‐IN 20 ). Recently, the similar results have been shown when the cocoa extract and D‐limonene were encapsulated in alginate beads (Lević and others ; Lupo and others ), as well as the case of T. serpyllum L. aqueous extract encapsulated in chitosan microbeads (Trifkovic and others ).…”
Section: Resultssupporting
confidence: 72%
“…For both systems, there was a gradual significant increase in shear viscosity with 248 increasing alginate concentration from around 0 to 0.05 % (w/w), followed by a much steeper 249 increase as the polysaccharide concentration was increased further. Other authors have also 250 reported a steep increase in the viscosity of nanoemulsions with increasing alginate 251 concentration above a certain concentration (Lević, et al, 2015). This increase is a result of 252 stronger chain-chain interactions in more concentrated biopolymer solutions, and tends to lead 253 to distinct non-Newtonian behavior (Manojlovic, Djonlagic, Obradovic, Nedovic, & 254 Bugarski, 2006).…”
Section: Statistical Analysis 221mentioning
confidence: 97%
“…Neki materijali poput polisaharida su pogodni za dobijanje inkapsulata ekstruzionim procesima [5,6], dok drugi materijali, poput voskova, su pogodniji za dobijanje čestica metodom emulzifikacije [7]. Sintetički materijali, kao na primer polivinil alkohol, su pak pogodni za dobijanje filmova sa inkapsulisanom aktivnom materijom, uz istovremeno postizanje željenih termičkih svojstava inkapsulisane aktivne komponente [8].…”
Section: Materijali Za Inkapsulacijuunclassified